Mengoptimalkan Pengimplementasian Pelatihan dan Pengembangan Pelayanan Tenaga Kerja kesehatan di RSUD Sawerigading - Dina Sarah Syahreza; Hilma Harmen; Grestin Analia; Nisa Nababan; Regita Cahyani; Rosana Girsang; Silvia Putriani; Tamara Marpaung (Economic Reviews Journal, 2024)
This article discusses the implementation of training and development of health workforce services at Sawerigading Hospital to overcome cases of discrimination between BPJS and non-BPJS patients. This research uses a literature review method with a qualitative approach and highlights the need for increased HR training and development for the optimization of health services. The results showed the importance of improving the skills, knowledge, and inclusive culture of health workers, as well as involving the community in efforts to improve service effectiveness. RSUD Sawerigading has committed to improving employee competencies through technical, soft skills, self-development, and specialization training programs to improve overall health services. Concrete steps are needed to address discrimination against BPJS patients and improve staff understanding of ethics and professionalism in health services to achieve optimal service.